The new Nicaraguan water law in context: Institutions and challenges for water management and governance - Novo, Paula; Garrido, Alberto (International Food Policy Research Institute, 2010)
The Nicaraguan Water Law, enacted in September 2007, is the first attempt to implement a new water law in the country. This is not an isolated legislative process in Central America, as other countries initiated similar reforms based on the Dublin principles. Although all new water laws need time to be implemented, the progress in Nicaragua has so far been meager. This paper provides a diagnosis about the Nicaraguan Water Law by identifying the major factors that may impede or delay its future implementation and enforcement. Its empirical underpinning is provided by 41 in-depth interviews among a sample of representative policy actors and stakeholders. The results show that the law's potential for solving water conflicts has yet to be seen in practice. Major barriers are found in the transaction costs of inter-institutional coordination, information gathering, property rights protection and enforcement, and strategic costs. For example, the institutional remapping grants new roles to old actors as well as old roles to new entities. In addition, sugarcane mills, rice, and coffee lobbies have presence in the legislative and block the appointment of managers in the newly created institutions. This paper argues that at the root of the problems is the inconsistency of setting advanced water objectives that land on weak institutions. Based on this, a number of prioritization, sequencing, and timing policy recommendations are drawn.